Drag-along and Tag-along Rights In The Perspective of Indonesian Company Law - Rinna Justisiana; Togi Pangaribuan (Fakultas Hukum, Universitas Warmadewa, 2022)
As technology develops in this Industrial Revolution of 4.0, technology companies have gained the spotlight among other business sectors. Many business actors are competing to establish a company or known as a start-up in the technology sector. These start-ups are also gaining attention from investors or venture capital companies interested in investing their funds for start-up growth. The fundraising to the company may be in the form of a debt, convertible note or equity. In terms of equity fundraising, as capital contribution or shares ownership, the founders of the start-up company will jointly partner with investors as the company’s shareholders. This cooperation usually regulated under shareholders’ agreement which some of the substances are rights and obligations of the shareholders. In addition to the rights of shareholders as regulated in Law Number 40 of 2007 on Limited Liability Company as lastly amended by Law Number 11 of 2020 on Job Creation or known as the Indonesian Company Law, Drag-Along Rights and Tag-Along Rights are commonly found under the modern-day investment-related shareholders’ agreement. However, these two rights are not explicitly governed in the Indonesian Company Law. This article will analyze relevant provisions under the Indonesian Company Law towards the Drag-Along Rights and Tag-Along Rights enforceability.